Nightly sleep-wake concordance and daily marital interactions - Gunn, Heather E. (Sleep Health, 2021)
OBJECTIVE: We and others have found that couples’ sleep is a shared and dyadic process. Couples’ sleep-wake concordance (whether couples are awake or asleep at the same time) is associated with couples’ relationship factors; however, we know little of the temporal associations between concordance and daily relationship characteristics. The purpose of this study was to examine daily positive and negative interpersonal interactions to determine how they predict, and are predicted by, nightly sleep-wake concordance. METHOD: Participants were 48 heterosexual couples between 18–45 years of age who shared a bed with their spouse. Couples completed questionnaires and daily assessments of positive and negative interactions. Each member of the dyad wore wrist actigraphs for 10 days. Sleep-wake concordance was calculated as the percentage of time couples were awake or asleep throughout the night at one-minute intervals. Multilevel modeling with lagged effects determined bidirectional and lagged associations between concordance and couples’ daily interactions. RESULTS: Couples had more negative interactions than their usual following nights with higher concordance than their usual (but not vice versa) and this was more pronounced for well-adjusted couples. In contrast, across all couples, more positive interactions and perceived warmth and support from partners was associated with higher concordance. CONCLUSIONS: Our findings demonstrate that the valence of sleep-wake concordance depends on relationship quality characteristics (e.g., marital adjustment). Future research on relationships, sleep, and health should consider couples’ shared sleep behaviors as one mechanism by which relationships are associated with long-term health outcomes.